Surto de anaplasmose associado com a presença de diferentes cepas de Anaplasma marginale em gado leiteiro dos estados de São Paulo e Goiás, Brasil - Machado, Rosangela Zacarias [UNESP]; da Silva, Jenevaldo Barbosa [UNESP]; André, Marcos Rogério [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; Matos, Carlos Antonio [UNESP]; Obregón, Dasiel [UNESP] (FapUNIFESP (SciELO), 2015)
The present study reports the genetic diversity of Anaplasma marginale during anaplasmosis outbreaks in rural properties of the states of Goiás and São Paulo, Brazil. Mortality rates of 3.5% (37/1,050) in calves, 4.7% (45/954) in heifers and 1.1% (25/2,200) in lactating cows were observed in a cattle herd of the municipality of Mambaí, state of Goiás, central-western Brazil. In a cattle herd from the municipality of Lins, state of São Paulo, in southeastern Brazil, none of the animals died, despite presenting clinical signs suggestive of bovine anaplasmosis and exhibiting a drastic decrease in milk production. Thus, blood samples were collected from 100 animals with clinical signs suggestive of bovine anaplasmosis in the municipalities of Mambaí and Lins. Based on the microsatellite structure of the MSP1a of A. marginale, the genotypes E and H were observed in Lins, and the C, D and E genotypes were found in Mambaí. The analysis of the tandem repeat structures of the MSP1a showed nine different strains (τ-10 -15, α-β2, α-β3-13, α-β2 192, τ-β-100, α-β2-Γ, 193-β-100, 191-13-Γ and 191-13-18) in Lins and two (α-β3-Γ and E-F-φ2-F2) in Mambaí. Three new tandem repeats of MSP1a (191, 192 and 193) were described. The τ-10-15 and α-β3-Γ strains were predominantly associated with the occurrence of clinical anaplasmosis and mortality in calves, heifers and lactating cows.
Outbreak of anaplasmosis associated with the presence of different Anaplasma marginale strains in dairy cattle in the states of São Paulo and Goiás, Brazil
Keywords: Anaplasmosis; Brazil; Dairy herd; Genotypes; MSP1a; Outbreaks